Take up your pen : unilateral presidential directives in American politics - Dodds, Graham G. (Democracy, citizenship, and constitutionalism., 2013)
The author explores the constitutional and historical development of unilateral presidential directives, the ability of presidents to bypass the legislative process and set public policy via their own executive orders, and how such a practice fits Americans' conception of democracy.